Sistem Informasi Geografis Pasangan Usia Subur Di Kelurahan Tamarundung Kota Palopo Berbasis Android - Nur, Andi Auliya Pratiwi; Sulaeman, Budiawan; Suppa, Rinto (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2021)
The purpose of this research is to create an application that can help visitors / couples of childbearing age see the locations and data of couples of childbearing age in Tamarundung village. Where the researchers directly went to the object of research, namely UPTD KB Tamarundung Village, Palopo City to obtain data and information about couples of childbearing age. The research method used is the Prototype method where the stages in this method are Requirements Collection, Prototyping building, Prototyping evaluation, coding, testing, system evaluation and system use. This Geographic information system in its manufacture uses PHP and MySQL as a database, Google MAPS API & Web Server is used to implement the program and is tested with Black Box testing techniques. With this geographic information system, it can help visitors/couples of childbearing age to view information such as data on couples of childbearing age, location of couples of childbearing age, location of UPTD KB in Tamarudung Village, Palopo City and make it easier for UPTD KB in Tamarundung Village to manage data for fertile age couples.